THE EVENT OF BREAST ENGORGEMENT ON MOTHERS WHO ARE UNDERGOING AND NOT UNDERGOING THE MATERNITY BLUES - nunuk nur hayati; partina - - (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2021)
Pregnancy and giving a birth are natural processes experienced by productive ages women; in this case the mothers will undergo several changes, either physically or psychologically. After giving a birth, some adjustments are required by mothers. Some of them are able to adjust themselves and some of them are not. Events, Reviews those Unable to adjust Themselves undergo a psychological disturbance the so-called